ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN DI PT SURYAGITA NUSARAYA DENGAN METODE REGRESI LINIER BERGANDA - Musahidin, Fayakun; Suhartini (Journal of Research and Technology, 2016)
PT Suryagita Nusaraya is a company engaged in the field of courier services in Surabaya. Since it is a good company that has qualified employees, it continuously makes efforts for the improvement of the welfare and advancement of employees. Judging from the current phenomena, there are number of employees who violate the rules that have been set by the management of PT Suryagita Nusaraya including: not punctual, often being absence, and leaving the company during working hours. The purpose of this study is to analyze the factors that most affect the job satisfaction of employees of PT Suryagita Nusaraya using multiple linear method. The independent variables used are work (X1), status (X2), boss (X3), colleagues (X4), and promotion (X5), while the dependent variable is employee satisfaction (Y). Here, the method used in this research is multiple linear regression. Based on statistical data analysis, the indicators in this study are valid and are reliable variables. In the classic assumption test, the regression of multicolinierity free model, there is no heteroskedastisitas for the data and it has normal distribution. The sequence of the most influential variables individually are as follows: status (X1) with a regression coefficient of 1.095, boss (X2) with a regression coefficient of 0.644, job (X3) with a regression coefficient of 0.084, and colleagues (X4) with a regression coefficient of 0.019, while the lowest influential variable is sale (X5) with a regression coefficient of - 0.066. Keywords: Employee, Multiple Linear Regression, Satisfaction, Service Delivery.